To investigate the role of fetoplacental prorenin, rennin EDRF and Endothelins in the Toxaemia of pregnancy - Singh, Harbindar Jeet (1999)
The main objective of the study was to investigate the role of Endothelin-1,EDRF,renin and prorenin in fetoplacental tissues.The precise pathogenesis of pre-eclampsia is still unknown but there is a generally held view that placental hypoperfusion,secondary to some vaso-active substance, may be responsible for this disease entity. Endothelin-I is a very powerful vasoconstrictor whereas EDRF is a vasodilator. Renin, through activation of the localized renin angiotensin system, may also work as a vasoconstrictor. Prorenin is being considered by some as not only a precursor of renin but, it by itself: as a vasodilator. We hypothesise that there probably exists an imbalance between the various vasodilator and vasoconstrictor substances in the placenta, more in favour of vasoconstrictors. This imbalance may be responsible for the placental vasoconstriction and consequently placental hypoperfusion. Our observations reveal significantly higher levels of endothelin-1 in fetoplacental tissues from women with pre-eclampsia We did not find any significant differences in renin activity or renin concentration in the fetoplacental tissues between the two groups. Total renin however was significantly higher in tissues from women with pre-eclampsia We were unable to measure EDRF in this study and therefore would find it difficult to precisely state the significance of these observations. But in another separate study, we have observed a lowered kallikrien-kinin (KKS)activity in placenta from women with pre-eclampsia KKS has vasodilator properties. It is possible therefore that EDRF activity may be similarly lowered. Nitric oxide synthetase activity has been observed to be lower in placentae from women with preeclampsia. From our observations it may be concluded, that there exists an abnormality in the expression of endothelin in the placenta and over production of this peptide may be responsible for some of the vasoconstriction and consequently hypoperfusion the placenta The raised prorenin may be a response to this vasoconstriction but its vasodilator response may be blunted. However more studies are needed to identify the cellular sources of these peptides in the placenta before it can be conclusively established that over production of endothelin-1 may indeed be the primary abnormality.